Targeting chromosomally unstable tumors with a selective KIF18A inhibitor - Aaron F. Phillips; Rumin Zhang; Mia Jaffe; Ryan Schulz; Marysol Chu Carty; Akanksha Verma; Tamar Y. Feinberg; Michael D. Arensman; Alan Chiu; Reka Letso; Nazario Bosco; Katelyn A. Queen; et al. (Nature Communications)
Abstract Chromosome instability is a prevalent vulnerability of cancer cells that has yet to be fully exploited therapeutically. To identify genes uniquely essential to chromosomally unstable cells, we mined the Cancer Dependency Map for genes essential in tumor cells with high levels of copy number aberrations. We identify and validate KIF18A, a mitotic kinesin, as a vulnerability of chromosomally unstable cancer cells. Knockdown of KIF18A leads to mitotic defects and reduction of tumor growth. Screening of a chemical library for inhibitors of KIF18A enzymatic activity identified a hit that was optimized to yield VLS-1272, which is orally bioavailable, potent, ATP non-competitive, microtubule-dependent, and highly selective for KIF18A versus other kinesins. Inhibition of KIF18A’s ATPase activity prevents KIF18A translocation across the mitotic spindle, resulting in chromosome congression defects, mitotic cell accumulation, and cell death. Profiling VLS-1272 across >100 cancer cell lines demonstrates that the specificity towards cancer cells with chromosome instability differentiates KIF18A inhibition from other clinically tested anti-mitotic drugs. Treatment of tumor xenografts with VLS-1272 results in mitotic defects leading to substantial, dose-dependent inhibition of tumor growth. The strong biological rationale, robust preclinical data, and optimized compound properties enable the clinical development of a KIF18A inhibitor in cancers with high chromosomal instability.